2008
DOI: 10.1111/j.1600-0501.2007.01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year results from a randomized, controlled trial on early and delayed loading of implants supporting full‐arch prosthesis in the edentulous maxilla

Abstract: The present randomized controlled trial showed no important differences between early and delayed loading of implants in the edentulous maxilla after 5 years of function. A favourable long-term marginal bone response to the sandblasted large-grit acid-etched (SLA) surface was observed. Technical complications were mainly resin-related which could be avoided by the use of a lingual gold onlay. It is concluded that early loading of SLA-surface implants for support of full-arch bridges represents a viable therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 31 publications
12
105
0
7
Order By: Relevance
“…12 A total of 142 non-submerged and surface modified implants (SLA) were placed. The patients were followed with annual clinical and radiographic examinations when the bridges were removed.…”
Section: Early Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A total of 142 non-submerged and surface modified implants (SLA) were placed. The patients were followed with annual clinical and radiographic examinations when the bridges were removed.…”
Section: Early Loadingmentioning
confidence: 99%
“…On the contrary, no bone volume or implant stability criteria were used in the study by Fischer et al 12 where 24 patients with edentulous maxillae were randomized into test and control groups. Implant lengths from 8 to 12 mm were used in both groups.…”
mentioning
confidence: 99%
“…In poor quality bone, survival rates were comparable with those from conventional or delayed loading. The mean bone level change was not deemed to be clinically significant and compared well with the typical bone resorption observed in conventional implant loading (Kinsel & Liss, 2007;Fischer et al, 2008). Several animal studies also reported favorable results when using immediate and early loading principles.…”
Section: Immediate and Early Loadingmentioning
confidence: 63%
“…Various surface treatments have been successfully used to achieve more rapid and more stable bone integration i.e. bone-metal anchorage (Buser et al 1999 ;Albrektsson et al 2000 ;Arvidson 1998 ;Arvidson et al 1998Arvidson et al , 2008Fischer et al 2008 , for recent reviews see, Esposito et al 2004Esposito et al , 2007aWennerberg and Albrektsson 2009 ).…”
Section: Loss Of Permanent Teethmentioning
confidence: 99%